AKTIVITAS KELOMPOK USAHA BERSAMA (KUB) MENJAHIT PADA POSDAYA MANDIRI RIAU BERSATU DI KOTA PEKANBARU - Dinda Rahayu; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to find out how the activities and functions of the sewing joint business group at Posdaya Mandiri Riau Unity. To obtain the results of the study, the researcher used descriptive quantitative methods, which involved the activities and functions of the sewing joint business group (KUB) at Posdaya Mandiri Riau Unity which would then be analyzed using structural functional theory. The formulation of the problem in this study (1) How is the activity of KUB sewing at the independent Riau Unit Posdaya in Pekanbaru City? (2) What is the function of the KUB in empowering members of the sewing community at the independent Riau Unit Posdaya in Pekanbaru City?. Data collection techniques in this study were in the form of questionnaires, and documentation. The population and samples using the saturated sample technique or census by making all the population as samples with the total population in this study as many as 72 members of the Kub Sewing Posdaya Mandiri Riau Unity. And the results of this study that from data analysis it is known that the sewing cub activities from socialization, training, and sewing are in the medium category, as weell as functions run by members in the form of manifest functions and latent functions are in the medium category. Keywords: Activities, KUB, Posdaya Mandiri Riau Bersatu